“Some distance between us”: a UK mixed methods study exploring experiences of remote care for eating disorders during COVID-19 - Murphy-Morgan, Claire; Brown, Richard; Love, Charlotte; Branley-Bell, Dawn (Frontiers in Psychiatry, 2024)
Introduction: COVID-19 necessitated a rapid move from face-to-face services to remote care for eating disorders/eating distress (EDs). This study explores the advantages and challenges of remote care, identifying future implications for service provision. Remote care has been considered in the broadest of terms, including therapeutic care (e.g., Cognitive Behavioural Therapy, peer support, forums, one-to-one and group care options). Methods: Using a mixed methods approach, data were collected from 211 people with lived experience of EDs (PWLE), with and without formal diagnosis. 27 participants took part in semi-structured interviews/workshops and a further 184 participants took part via an online survey. Participants reported on their ED status, the impact of the pandemic on symptoms, the benefits, and challenges of remote care (and type of support accessed), and any reasons for not accessing support. Participants were invited to make future care recommendations. Results: ED symptoms were reported as worsening during the pandemic with contributing factors including isolation, lack of routine, negative emotions, and feeling like the external situation was outside of one's control. Remote care was positively attributed to increased flexibility and facilitation of social connection. Identified barriers to access included lack of awareness about support availability, digital access/literacy, and competing commitments. Further challenges included approaches being perceived as too clinical (e.g., ED information and support presented using clinical language and/or limited to support within medical care settings, without acknowledging the broader context of disordered eating), uncertainty around remote care quality, and concerns that remote platforms may facilitate masking of symptoms. Participants reported distress caused by online platforms where self-view is the default during video calls. They expressed a need for more holistic approaches to remote care, including: "real stories" of recovery, and hybrid (online and offline) options for greater flexibility and widening of access and choice. Participants also expressed a need for appropriate digital literacy training. Discussion: Future recommendations emphasise user-centered holistic and hybrid approaches to ED remote support, with training to address digital literacy barriers and facilitate user control of platform functionalities (e.g., self-view). This study underscores the need for continued remote care with a focus on inclusivity and user empowerment.